2007
DOI: 10.1097/mat.0b013e31805370e3
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Right Ventricular Pacing on Cardiac Apex Rotation Assessed by a Gyroscopic Sensor

Abstract: To quantify cardiac apex rotation (CAR), the authors recently proposed the use of a Coriolis force sensor (gyroscope) as an alternative to other complex techniques. The aim of this study was to evaluate the effects of right ventricular (RV) pacing on CAR. A sheep heart was initially paced from the right atrium to induce a normal activation sequence at a fixed heart rate (AAI mode) and then an atrioventricular pacing was performed (DOO mode, AV delay ‫؍‬ 60 ms). A small gyroscope was epicardially glued on the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
8
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 53 publications
2
8
0
Order By: Relevance
“…Furthermore, precise assessment of systolic and diastolic function, and LV dyssynchrony can be simultaneously achieved 8. Marcelli et al reported that right ventricular pacing, which is known to cause LV dyssynchrony,9 altered diastolic untwisting velocity in sheep, suggesting a possible link between torsional behaviour and dyssynchrony 10. Therefore, we hypothesised that echocardiographic parameters, including LV dyssynchrony, could be associated with LV untwisting in addition to torsional deformation.…”
mentioning
confidence: 90%
“…Furthermore, precise assessment of systolic and diastolic function, and LV dyssynchrony can be simultaneously achieved 8. Marcelli et al reported that right ventricular pacing, which is known to cause LV dyssynchrony,9 altered diastolic untwisting velocity in sheep, suggesting a possible link between torsional behaviour and dyssynchrony 10. Therefore, we hypothesised that echocardiographic parameters, including LV dyssynchrony, could be associated with LV untwisting in addition to torsional deformation.…”
mentioning
confidence: 90%
“…Accelerometer is very susceptible to earth gravity which makes it more prone to vibration/noise. Whereas, gyroscope is not affected by the gravity of earth and is insusceptible to axial and radial translational motions [14]. Additionally, gyroscope is an active sensor that consumes more power than accelerometer which is a passive sensor.…”
Section: Discussionmentioning
confidence: 99%
“…The results collected from preliminary evaluations on animals (73)(74)(75) demonstrated the feasibility of assessing cardiac rotation by means of a gyro sensor epicardially attached to the cardiac apex and its capability of detecting alterations of cardiac function experimentally induced (acute ischemia by coronary artery ligation, change in cardiac contractility by dobutamine infusion, and asynchronous cardiac contraction by pacing). Although this new sensor seems to have great potential in cardiac function monitoring, further animal evaluations are needed to confirm its long-term efficacy.…”
Section: An Implantable Sensor For Measuring Cardiac Apex Rotationmentioning
confidence: 99%